2019
DOI: 10.3390/s19040929
|View full text |Cite
|
Sign up to set email alerts
|

Fault Identification of Chemical Processes Based on k-NN Variable Contribution and CNN Data Reconstruction Methods

Abstract: Data-driven fault detection and identification methods are important in large-scale chemical processes. However, some traditional methods often fail to show superior performance owing to the self-limitations and the characteristics of process data, such as nonlinearity, non-Gaussian distribution, and multi-operating mode. To cope with these issues, the k-NN (k-Nearest Neighbor) fault detection method and extensions have been developed in recent years. Nevertheless, these methods are primarily used for fault de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“… is the half-wave switching voltage of the two modulators, and are the modulation indexes of MZM1 and MZM2. The two MZMs are operated in a push-pull mode, which helps in achieving balanced modulation and cancellation of unwanted signals [ 44 ].…”
Section: Theoretical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“… is the half-wave switching voltage of the two modulators, and are the modulation indexes of MZM1 and MZM2. The two MZMs are operated in a push-pull mode, which helps in achieving balanced modulation and cancellation of unwanted signals [ 44 ].…”
Section: Theoretical Analysismentioning
confidence: 99%
“…Additionally, a modified CNN model has been presented that uses a random forest (RF) classifier [ 43 ]. A data reconstruction method based on k-Nearest Neighbour (k-NN) variable contribution and convolutional neural network (CNN) is proposed to extract effective error information [ 44 ]. A network comprising of CNN layers and a multi-output regressor is proposed to estimate points [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…Applications in sensor networks include intrusion detection systems [ 6 , 7 ], fault detection [ 8 ], fault identification [ 9 ], fault classification [ 10 ], fall prediction [ 11 ], indoor localisation [ 12 , 13 ], etc. The intrusion detection system [ 6 ] can distinguish between unusual and common nodes by monitoring their anomalous actions.…”
Section: Applicationsmentioning
confidence: 99%
“…Cai et al [16] demonstrated a prototype with an appropriate classification tool for successfully discriminating the gender of silkworm by X-ray imaging the cocoons. Shape features such as major axis, minor axis, ratio of major axis to minor axis, eccentricity, roundness, rectangularity, complexity, concave and convex characteristics of the chrysalis are extracted from X-ray images and inputted to pre-trained classifiers such as k-Nearest Neighbor (kNN) [17], Linear Discriminant Analysis (LDA) [18], Neural Networks (NN) [19] and Support Vector Machine (SVM) [20] to accurately classify the cocoons as male or female. The authors considered 1071 samples from three hybrid breeds and have reported an accuracy of 93.68% with kNN classifier.…”
Section: Introductionmentioning
confidence: 99%